Comprehensive profiling of serotypes, antimicrobial resistance and virulence of Salmonella isolates from food animals in China, 2015–2021 - Guo, Lili; Xiao, Tianan; Wu, Liqin; Li, Yan; Duan, Xiaoxiao; Liu, Wenhua; Liu, Kaidi; Jin, Wenjie; Ren, Hao; Sun, Jian; Liu, Yahong; Liao, Xiaoping; et al. (Frontiers in Microbiology, 2023)
Salmonella is a ubiquitous foodborne pathogen and mainly transmitted to humans along the farm-to-fork chain through contaminated foods of animal origin. Thus, the aim of this study was to investigate the serotypes, antimicrobial resistance and virulence of Salmonella from China. Here, a total of 617 Salmonella isolates were collected from 4 major food animal species across 23 provinces in China from 2015-2021. Highest Salmonella prevalence were observed in Guangdong (44.4%) and Shandong (23.7%). Chickens (43.0%) was shown to be the major source of Salmonella contamination, followed by pigs (34.5%) and ducks (18.5%). The number of Salmonella increased significantly from 5.51% to 27.23% during 2015-2020. S. Derby (17.3%), S. Enteritidis (13.1%) and S. Typhimurium (11.4%) were the most common serotypes among 41 serotypes identified in this study. Antibiotic susceptibility testing showing that the majority of the Salmonella isolates were resistant to neomycin (99.7%), tetracycline (98.1%), ampicillin (97.4%), sulfadiazine/trimethoprim (97.1%), nalidixic acid (89.1%), doxycycline (83.1%), ceftriaxone (70.3%), spectinomycin (67.7%), florfenicol (60.0%), cefotaxime (52.0%) and lomefloxacin (59.8%). The rates of resistance to multiple antibiotics in S. Derby and S. Typhimurium were higher than that in S. Enteritidis. However, the rate of resistance to fosfomycin were observed from higher to lower by S. Derby, S. Enteritidis, and S. Typhimurium. Biofilm formation ability analysis found that 88.49% of the Salmonella were able to produce biofilms, of which 236 Salmonella isolates were strong biofilm producer. Among the 26 types of antibiotics resistance genes (ARGs) were identified in this study, 4 ARGs (tetB, sul2, aadA2, and aph(3’)-IIa) were highly prevalent. In addition, 5 β-lactam resistance genes (blaTEM, blaSHV, blaCMY-2, blaCTX-M, and blaOXA) and 7 quinolone resistance genes (oqxA, oqxB, qnrB, qnrC, qnrD, qnrS, and qeqA) were detected among these isolates. 12 out of 17 virulence genes selected in this study were commonly presented in the chromosomes of tested isolate, with a detection rate of over 80%, including misL, spiA, stn, pagC, iroN, fim, msgA, sopB, prgH, sitC, ttrC, spaN. This study provided a systematical updating on surveillance on prevalence of Salmonella from food animals in China, shedding the light on continued vigilance for Salmonella in food animals.